Comparison of vacuum pressures and suction forces generated by different pump systems for aspiration thrombectomy - Kim, Sum; Lee, Jong Young (Frontiers in Neurology, 2022)
Objective Aspiration thrombectomy is used to treat endovascular stroke treatment by clot removal through vacuum and suction forces. We aimed to investigate the pressures and suction forces generated by different pump systems for aspiration. Methods Vacuum pressure was measured using a vacuum gauge with a closed tip for a 60cc syringe and aspiration pumps. Using an artificial thrombus made from polyvinyl alcohol hydrogel and latex membrane, we assessed the catheter tip force generated on an artificial thrombus using 5Fr Sofia and 6Fr Sofia PLUS intermediate catheters combined with Penumbra Jet Engine or Stryker Medela AXS Universal Aspiration Set. Subsequently, we calculated the catheter tip forces based on the pressure [catheter tip size (force = area × pressure)], and compared with the measured catheter tip force. Results The 60cc syringe generated the highest vacuum pressure. Among the automatic pumps, the Penumbra jet engine generated the highest vacuum pressure. The catheter tip forces on the artificial thrombus and latex membrane were 18.5 ± 1.70 and 8.0 ± 1.23 gf, respectively, and 13.9 ± 1.37 and 5.6 ± 0.83 gf, respectively using the 5 Fr Sofia with the Penumbra Jet Engine and the Stryker Medela AXS Universal Aspiration Set, respectively. The corresponding values for the 6 Fr Sofia PLUS with the Penumbra Jet Engine and Stryker Medela AXS Universal Aspiration Set were 39.7 ± 3.88 and 20.7 ± 0.92 gf and 25.4 ± 4.96 and 18.0 ± 0.84 gf. For a constant catheter diameter and the automatic pump, the catheter tip force was significantly larger in the artificial thrombus than latex membrane (p < 0.001, ANOVA). Conclusion The catheter diameter, vacuum pressure, and clot softness are positively correlated with the catheter tip force.